2018
DOI: 10.3390/coatings8070230
|View full text |Cite
|
Sign up to set email alerts
|

Repair Bond Strength of a Resin Composite to Plasma-Treated or UV-Irradiated CAD/CAM Ceramic Surface

Abstract: Abstract:The aim of this study was to investigate whether atmospheric-pressure plasma (APP) or ultraviolet (UV) irradiation could alter the hydrophilicity of a computer-aided design/computer-aided manufacturing (CAD/CAM) glass ceramic surface, and thereby enhance the repair bond strength between the ceramic and a resin composite. Forty-eight leucite-reinforced glass ceramic discs were treated with 40% phosphoric acid and randomly assigned into one of six groups: Group 1, control; Group 2, treated with a mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Silane is recommended for enhancing the bonding capacity between silica-based ceramics and resin through the existence of hydroxyl and organofunctional groups in silane, which respectively bond to silica and resin. 37 However, silane can not only act as an adhesion promoter but also increasing the wettability and bond strength. 38 Beautifil II, composed of a multifunctional glass filler and S-PRG filler based on a nano-hybrid type fluroboroaluminosilicate glass, at a filler loading of 83.3 wt%, 39 was the target for chemical reaction with silane in ceramic restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Silane is recommended for enhancing the bonding capacity between silica-based ceramics and resin through the existence of hydroxyl and organofunctional groups in silane, which respectively bond to silica and resin. 37 However, silane can not only act as an adhesion promoter but also increasing the wettability and bond strength. 38 Beautifil II, composed of a multifunctional glass filler and S-PRG filler based on a nano-hybrid type fluroboroaluminosilicate glass, at a filler loading of 83.3 wt%, 39 was the target for chemical reaction with silane in ceramic restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of restorations' inner surfaces is a critical step in which high pressurized particle abrasion or strong acids (i.e., hydrofluoric acid—HF) can be used [ 23 , 24 ]. However, in Japan, hydrofluoric acid cannot be used by dental clinicians since a 3-year-old child patient died of acute drug intoxication from hydrofluoric acid in 1982 when fluoride solution was misplaced by the acid [ 25 ]. Thus, nowadays, dentists cannot buy HF acid, and they rely on the dental technician for the HF application.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nowadays, dentists cannot buy HF acid, and they rely on the dental technician for the HF application. Alternatively, the dentist would use phosphoric acid to etch before the silane coating is applied [25][26][27]. More recently, a hypersaturated solution of zirconium oxide particles in sodium hydroxide and water has been introduced and showed an effective decontamination potential to clean zirconium surface by removing its organic contents [28][29][30]).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, phosphoric acids are relatively safer and do not produce any compounds that decrease the bond strength and are non-washed easily ( 34 ). Phosphoric acid may minimally roughen surfaces ( 34,37 ), but can neutralize the alkalinity of the absorbed water layer on the ceramic surface, thus contributing to the chemical activity of the ceramic primer that is subsequently applied ( 33 ). It has been reported that bond strength between ceramic and cement may increase when phosphoric acid is used with ceramic primer ( 34 ).…”
mentioning
confidence: 99%